Determinant of Tax Aggressiveness and Relationship with Firm Value (Empirical Study Company Listed Go-Public in Indonesia Stock Exchange) - Hitten, Akhmad; Novita, Novita (Fakultas Ekonomi dan Bisnis, UNTAN, 2020)
This study aims to determine the effect of liquidity, profitability, and solvability on the level of tax aggressiveness with firm value as a control variable. Total sample was 86 non-financial company that implicate tax aggressiveness in Indonesia Stock Exchange (IDX), with purposive sampling, with cross section data period 2007 to 2017. This study using agency theory and signaling theory as the grand theory. The data were analyzed using Structural Equation Modeling- Partial Least Square (SEM-PLS). This study uses a SmartPLS 3.0 and must pass outer and inner criteria. The reason why the author choose SmartPLS is because this application program can explain each indicator of the variable, so will be easy to evaluate which indicator that not have the correspondent affect with the dependend variable. The previous studies of ETR showed inconsistent results in various countries. Test results show that liquidity and profitability have a negative and significant influenced with tax aggressiveness. Solvability has a negative and not significant influenced on tax aggressiveness. Firm value has a positive and significant influenced on tax aggressiveness.